Role of the Microbiome in Interstitial Lung Diseases - Chioma, Ozioma S.; Hesse, Laura E.; Chapman, Austin; Drake, Wonder P. (Frontiers in Medicine, 2021)
There are trillions of microorganisms in the human body, consisting of bacteria, viruses, fungi and archaea; these collectively make up the microbiome. Recent studies suggest that the microbiome may serve as a biomarker for disease, a therapeutic target, or provide an explanation for pathophysiology in lung diseases. Studies describing the impact of the microorganisms found in the respiratory tract on lung health have been published and are discussed here in the context of interstitial lung diseases. Additionally, epidemiological and experimental evidence highlights the importance of cross-talk between the gut microbiota and the lungs, called the gut–lung axis. The gut-lung axis postulates that alterations in gut microbial communities may have a profound effect on lung disease. Dysbiosis in the microbial community of the gut is linked with changes in immune responses, homeostasis in the airways, and inflammatory conditions in the gastrointestinal tract itself. In this review, we summarize studies describing the role of the microbiome in interstitial lung disease and discuss the implications of these findings on the diagnosis and treatment of these diseases. This paper describes the impact of the microbial communities on the pathogenesis of lung diseases by assessing recent original research and identifying remaining gaps in knowledge.